Global Trends in Normativity and Regulatory Issues on Nanotechnology (2023)
This article presents a comprehensive analysis of global trends in normativity and regulatory issues in nanotechnology through a bibliometric study. To conduct this analysis, keywords such as regulations, legislation, policy, nanotechnology, nanomaterials, nanoparticle, and risk were employed. The search generated a total of 1202 refined scientific papers and 4914 patents. Various aspects were evaluated, including articles with the highest number of citations, countries with the highest academic production, institutions with the most documents, influential authors, author correlations, and keyword analysis, among others. The Scopus and Journal citation report databases, the VosViewer software, and different computer tools such as OpenRefine and Excel were used to conduct the analysis. The results point the United States (33.5%) as the country with the highest production, followed by the United Kingdom (10.9%), India (10.3%), and Germany (6.7%). Additionally, the results revealed some cooperation between the United States, United Kingdom, and Germany by 2014 and between China and India by 2018 and 2019. Moreover, according to the keyword analysis, only 10% of the scientific production speaks directly about regulations and policies on the effects on human health, with minor impact on the environment.